Crop-type-driven changes in polyphenols regulate soil nutrient availability and soil microbiota - Fan, Dongmei; Zhao, Zhumeng; Wang, Yu; Ma, Junhui; Wang, Xiaochang (Frontiers in Microbiology, 2022)
Crop rotation is a typical agronomic practice to mitigate soil deterioration caused by continuous cropping. However, the mechanisms of soil biotic and abiotic factors in response to different cropping patterns in acidic and polyphenol-rich tea nurseries remain unclear. In this study, the composition and function of microbial communities were comparatively investigated in soils of tea seedlings continuously planted for two years (AC: autumn-cutting; SC: summer-cutting) and in soils rotation with strawberries alternately for three years (AR: autumn-cutting). The results showed that AR significantly improved the survival of tea seedlings but greatly reduced the contents of soil polyphenols. The lower soil polyphenol levels in AR were associated with the decline of nutrients (SOC, TN, Olsen-P) availability, which stimulate the proliferation of nutrient cycling-related bacteria and mixed-trophic fungi, endophytic fungi and ectomycorrhizal fungi, thus further satisfying the nutrient requirements of tea seedlings. Moreover, lower level of polyphenols facilitated the growth of plant beneficial microorganisms (Bacillus, Mortierella, etc.) and supressed pathogenic fungi (Pseudopestalotiopsis, etc.), creating a more balanced microbial community that is beneficial to plant health. Our study broadens the understanding of the ecological role of plant secondary metabolites and provides new insights into the sustainability of tea breeding.